Pelatihan Dan Pendampingan Penyusunan Modul Ajar Bagi Guru MADIN Al-Qodiri Jember - Ansori, Muhamad (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2025)
The main function and duties of teachers in formal and non-formal education units are to carry out learning. To implement learning to be effective and programmed, teachers must prepare learning plans carefully. One of the learning plans prepared by the teacher is at least a teaching module. There is a lack of understanding about Teaching Modules for teachers, so that teachers at Madrasah Diniyah Al-Qodiri Jember never create Teaching Modules. As a solution, training and mentoring is provided with the aim of increasing teacher motivation, understanding and ability in compiling Teaching Modules. The results of this activity show that 100% of teachers' motivation is very good in participating in training and mentoring activities in preparing Teaching Modules, 79.15% of ustadz and ustadzah understand the training and mentoring material, and 70.32% of Madrasah Diniyah Al-Qodiri Jember teachers have been able to prepare Teaching Modules . The results of this community service activity show good results and help teachers in preparing Teaching Modules as guidelines and signs for implementing programmed and effective learning. Keywords: Teaching Module, Teacher